Effect of Equal Channel Angular Extrusion on the Thermal Conductivity of an AX52 Magnesium Alloy - Zuzanka Trojanová; Kristýna Halmešová; Ján Džugan; Zdeněk Drozd; Peter Minárik; Pavel Lukáč (Crystals, 2020)
An AX52 magnesium alloy (nominal composition Mg-5Al-2Ca in w.%) was submitted to equal channel angular pressing (ECAP) using processing route A; 1–8 passes through the ECAP tool were applied. The thermal conductivity of the ECAP samples was measured using a flash method in the temperature interval from room temperature up to 350 °C. The microstructure and texture of the samples were studied by light and electron microscopy. The severe plastic deformation, realized by the ECAP, influences the thermal properties of the alloy. The possible microstructural parameters determining the thermal conductivity were analyzed. New dislocations, the grain, phase boundaries, and texture of the samples may perceptibly change the thermal properties.